Prophylactic and therapeutic insights into trained immunity: A renewed concept of innate immune memory. Issue 1 (31st January 2022) - Bindu, Suresh; Dandapat, Satyabrata; Manikandan, Rajendran; Dinesh, Murali; Subbaiyan, Anbazhagan; Mani, Pashupathi; Dhawan, Manish; Tiwari, Ruchi; Bilal, Muhammad; Emran, Talha Bin; Mitra, Saikat; Rabaan, Ali A.; et al.
ABSTRACT: Trained immunity is a renewed concept of innate immune memory that facilitates the innate immune system to have the capacity to remember and train cells via metabolic and transcriptional events to enable them to provide nonspecific defense against the subsequent encounters with a range of pathogens and acquire a quicker and more robust immune response, but different from the adaptive immune memory. Reversing the epigenetic changes or targeting the immunological pathways may be considered potential therapeutic approaches to counteract the hyper-responsive or hypo-responsive state of trained immunity. The efficient regulation of immune homeostasis and promotion or inhibition of immune responses is required for a balanced response. Trained immunity-based vaccines can serve as potent immune stimuli and help in the clearance of pathogens in the body through multiple or heterologous effects and confer protection against nonspecific and specific pathogens. This review highlights various features of trained immunity and its applications in developing novel therapeutics and vaccines, along with certain detrimental effects, challenges as well as future perspectives.